Is the Understanding Dementia Massive Open Online Course Accessible and Effective for Everyone? Native Versus Non-Native English Speakers - Kim, Sarang; Bindoff, Aidan; Farrow, Maree; McInerney, Fran; Borchard, Jay; Doherty, Kathleen (International Review of Research in Open and Distributed Learning, 2021)
Most massive open online courses (MOOCs) are offered in English, including those offered by non-English speaking universities. The study investigated an identified English language dementia MOOC’s accessibility and effectiveness in improving the dementia knowledge of non-native English speaker participants. A total of 6,389 enrolees (age range 18–82 years; 88.4% female) from 67 countries was included in analyses. Dementia knowledge was measured by the Dementia Knowledge Assessment Scale (DKAS) before and after the MOOC completion. Rates of completion were also compared. Native English speakers (n = 5,320) were older, more likely to be female, less likely to be employed, and had lower educational attainment than non-native English speakers (n = 1025). Native English speakers were also more likely to care for or have cared for a family member or friend living with dementia than were non-native English speakers. Native English speakers had a significantly higher DKAS score both pre- (M = 33.0, SD = 9.3) and post-MOOC (M = 44.2, SD = 5.5) than did non-native English speakers (M = 31.7, SD = 9.1; and M = 40.7, SD = 7.7 for pre- and post-MOOC, respectively). Non-native English speakers with low pre-MOOC dementia knowledge scores gained significantly less dementia knowledge following course completion than did native English speakers (p <.001, adjusted for age and education). There was no significant difference between the two groups in their likelihood of completing the MOOC. Our findings suggest that non-native English speakers are motivated and able to complete the MOOC at similar rates to native English speakers, but the MOOC is a more effective educational intervention for native English speakers with low dementia knowledge.